ISLAMIC CHARACTER DEVELOPMENT THROUGH BOARDING-BASED PUBLIC SCHOOLS: INTERNALIZATION ISLAMIC METHODS - Nur Rizqi Febriandika; Chori Miftahul Kosidatul Natus (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2021)
This study aims to explain and identify the methods used in internalizing Islamic characters in boarding-based public schools. Public schools that implement a boarding system have a unique and special character. It is different from Islamic education which has been firmly embedded in schools that have been based on pesantren since the beginning. This research is descriptive qualitative, with data collection methods through observation, interviews, and documentation. The results of this study show that internalization of Islamic characters through subjects in the dormitory, such as the study of classical Islamic books (Fiqhu Sunnah, Aqidatul Awwan, Bidayatul Mujtahid, etc) and self-development activities in the form of extracurricular and organizational activities. The used methods are the wisdom method, exemplary method, habitual method, mauidzah method, and the reward and punishment method. Unlike pesantren culture which is closely tied to the figure of the kyai, the dormitory-based State Islamic schools tend to be weak in terms of the initiative and charisma of the kyai who the leaders are. Individually, kyai figures in boarding-based public boarding schools do not have as strong a role as those in pesantren. However, the ustad and coach figures play a collective and joint role in building students' Islamic character.Keywords: Islamic Character, Madrasah Aliyah, Boarding System, Public Schools